(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Dr. B R Ambedkar was the mild educationist and reformer with high constitutional knowledge. He studied all the progressive constitutions of contemporary life and narrated constitution of India, which is the standard constitution of the world. His efforts towards eradicating several social evils, and discrimination on the basis of caste, class , colour , gender, race language and geographical locations are addressed in his series of speeches and he discovered solutions for them through constitutional efforts. His commitment towards social reforms and development was constant. He was restless in giving justice and dignity to the deprived society. Non -institutional reformative practice was started long back in India and it got acceleration after legalized efforts of Dr. B R Ambedkar towards welfare of the deprived society. Efforts to understand Dr. B R Ambedkar as a social reformer and empowerment of deprived society. Descriptive research methodology used for this purpose and secondary sources of data is used.